Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Wirausahawan Terhadap Pentingnya Pembukuan Dan Laporan Keuangan - Solikah, Mar atus; Astuti, Puji; Paramitha, Dyah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2017)
The entrepreneur is one of the important players in the economic development of a region. In many countries, entrepreneurs with various business had a lot to contribute in addressing unemployment, to absorb the labor force that has not accommodated by other sectors. Entrepreneurs are required to identify new opportunities, new product, new production methods and marketing, manage capital and manage all aspect of the company. Activities undertaken by an entrepreneur in developing a business is often constrained by the problem of capital and marketing of its products. This relates to the condition of the difficulty small-scale companies to be able to provide adequate financial reports. Awareness of the importance of bookkeeping and financial statements arise when having to deal with banks or other institutions that require adequate financial statements. Based on these weaknesses, it is necessary to study in order to examine the factors that influence the perception of entrepreneurs associated with the importance of bookkeeping and financial statements. Respondents in this study are all entrepreneurs who have a business area of ​​the business center for digital printing and cutting sticker in Bangsal Kediri totaling 30 entrepreneurs. Data obtained through a questionnaire, and then analyzed using SPSS for Windows version 23.0 chi-square test. The results of the analysis that there is a relationship between educational background, level of education, size of business, length of business, and the business experience with the perception of the importance of bookkeeping and financial reporting with significance values less than 0.05.